2001
DOI: 10.1053/jhep.2001.26086
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Antiviral Effect on Hepatitis C Viral Dynamics in Serum and Peripheral Blood Mononuclear Cells During Combination Therapy With High–Dose Daily Interferon Alfa Plus Ribavirin and Intravenous Twice–Daily Treatment With Interferon Beta

Abstract: Hepatitis C virus (HCV) is known to infect and replicate within peripheral blood mononuclear cells (PBMC), thereby enabling the direct evaluation of antiviral mechanisms by analyzing HCV dynamics in PBMC. To address potential molecular differences associated with distinct antiviral regimens, we studied HCV dynamics in both serum and PBMC in 44 patients with HCV genotype 1b and high viral load who were randomly assigned to the following 4 different treatment groups: 1) combination therapy with 6 MU daily of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 47 publications
1
61
0
Order By: Relevance
“…Several studies comparing the safety of IFNβ and IFNα have been performed [29,30,[38][39][40][41][42] . Frosi et al [38] compared IFNα and IFNβ in 20 naïve patients treated for 6 months and did not observe any significant differences between the two treatment groups in terms of the frequency of adverse events.…”
Section: Clinical Studies Comparing the Safety Of Ifnβ To Ifnαmentioning
confidence: 99%
“…Several studies comparing the safety of IFNβ and IFNα have been performed [29,30,[38][39][40][41][42] . Frosi et al [38] compared IFNα and IFNβ in 20 naïve patients treated for 6 months and did not observe any significant differences between the two treatment groups in terms of the frequency of adverse events.…”
Section: Clinical Studies Comparing the Safety Of Ifnβ To Ifnαmentioning
confidence: 99%
“…Interestingly, considering viral dynamics such as virus half-life, the suppressing effect on viral replication observed through treatment appears consistently slower in PBMCs than in serum. 20 On the basis of these studies, one can argue that a specific replicative dynamics of HCV exists in PBMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, considering viral dynamics such as virus half-life, the suppressing effect on viral replication observed through treatment appears consistently slower in PBMCs than in serum. 20 On the basis of these studies, one can argue that a specific replicative dynamics of HCV exists in PBMCs.The relationship between quasispecies and replication in PBMCs is unclear. In a previous study we demonstrated, in the serum of a patient chronically infected with HCV, 21 the coexistence of internal ribosome entry site (IRES) quasispecies segregating according to their respective translation efficiencies in lymphoid and nonlymphoid optimal IRES.…”
mentioning
confidence: 99%
“…These observations demonstrate that while the half-life of venously-administered IFN-β in the blood is very short, the blood levels are maintained in the effective treatment range with twice daily administration (15). In addition, Asahina et al analyzed HCV dynamics in serum and peripheral blood mononuclear cells and demonstrated that twice daily administration of IFN-β exhibited a strong antiviral effect until the second phase (16).…”
Section: Discussionmentioning
confidence: 95%